PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN QUIZIZZ DI KELAS V SDN 15 AIE ANGEK KABUPATEN TANAH DATAR - Tunnisa, Zahra; Atri Waldi; Ranti Meizatri; Reinita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the improvement of student learning outcomes in Pancasila Education learning using the Problem Based Learning model assisted by Quizizz in class V SDN 15 Aie Angek, Tanah Datar Regency. This type of research is Classroom Action Research (CAR) with a qualitative and quantitative approach. The research was conducted in two cycles, where cycle I consisted of two meetings and cycle II one meeting. The subjects in this study were teachers (researchers) and 20 students. Data collection techniques used observation, tests, and non-tests. The results of the study showed an increase in: 1) Cycle I teaching modules with an average of 80.56% (Good), increasing in cycle II to 91.67% (Very Good). 2) Implementation of teacher activities in cycle I an average of 82.14% (Good), increasing in cycle II to 92.86% (Very Good). Student activity also increased from an average of 78.58% (Enough) in cycle I to 89.29% (Good) in cycle II. 3) Student learning outcomes increased from an average of 77.48 in cycle I to 88.54 in cycle II.Thus, it can be concluded that the application of the Problem Based Learning model assisted by Quizizz is effective in improving student learning outcomes in Pancasila Education learning in class V SDN 15 Aie Angek. Keywords: learning outcomes, Pancasila Education, Problem Based Learning, Quizizz